Algeria : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Algeria. (IMF Staff Country Reports; Country Report ;, 2009)
Algeria has enjoyed several years of strong economic performance, but continues to face important challenges. This 2008 Article IV Consultation highlights that economic performance of Algeria has remained relatively favorable in 2008. The outlook remains encouraging despite the challenging international environment. Executive Directors have welcomed Algeria's strong economic performance in recent years, with solid nonhydrocarbon growth and low inflation. They have also commended the authorities for their sound policy stance that has enabled the accumulation of large external reserves and resources in the oil stabilization fund.